Cadillac desert : the American West and its disappearing water - Reisner, Marc. (New York, N.Y., U.S.A. : Penguin Books, 1993)
This history of water rights in the American West focuses on the political corruption and intrigue, including the rivalry between the Bureau of Reclamation and the U.s. Army Corps of Engineers.
A country of illusion -- The Red Queen -- First causes -- An American Nile (I) -- The Go-Go years -- Rivals in crime -- Dominy -- An American Nile (II) -- The peanut farmer and the pork barrel -- Chinatown -- Those who refuse to learn ... -- Things fall apart -- A civilization, if you can keep it.
Maps on lining papers.
Includes bibliographical references (p. [522]-564) and index.
Keywords: Irrigation -- Government policy -- West (U.S.) -- History; Water resources development -- Government policy -- West (U.S.) -- History; Political corruption -- West (U.S.) -- History